Can I use TA? Should I use TA? Should I not use TA? Comparing reflexive thematic analysis and other pattern‐based qualitative analytic approaches. Issue 1 (18th October 2020) - Braun, Virginia; Clarke, Victoria
Abstract: Thematic analysis methods, including the reflexive approach we have developed, are widely used in counselling and psychotherapy research, as are other approaches that seek to develop 'patterns' (themes, categories) across cases. Without a thorough grounding in the conceptual foundations of a wide variety of across‐case analytic approaches, and qualitative research more broadly—something rarely offered in counselling training—it can be difficult to understand how these differ, where they overlap, and which might be appropriate for a particular research project. Our aim in this paper is to support researchers in counselling and psychotherapy to select an appropriate across‐case approach for their research, and to justify their choice, by discussing conceptual and procedural differences and similarities between reflexive thematic analysis (TA) and four other across‐case approaches. Three of these are also widely used in counselling and psychotherapy research—qualitative content analysis, interpretative phenomenological analysis and grounded theory. The fourth—discourse analysis—is less widely used but importantly exemplifies the critical qualitative research tradition. We contextualise our comparative approach by highlighting the diversity within TA. TA is best thought of as a spectrum of methods—from types that prioritise coding accuracy and reliability to reflexive approaches like ours that emphasise the inescapable subjectivity of data interpretation. Although reflexive TA provides the point of comparison for our discussion of other across‐case approaches, our aim is not to promote reflexive TA as 'best'. Rather, we encourage the knowing selection and use of analytic methods and methodologies in counselling and psychotherapy research.